2019
DOI: 10.1186/s12864-019-6006-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide and evolutionary analysis of the class III peroxidase gene family in wheat and Aegilops tauschii reveals that some members are involved in stress responses

Abstract: Background The class III peroxidase (PRX) gene family is a plant-specific member of the PRX superfamily that is closely related to various physiological processes, such as cell wall loosening, lignification, and abiotic and biotic stress responses. However, its classification, evolutionary history and gene expression patterns are unclear in wheat and Aegilops tauschii . Results Here, we identified 374, 159 and 169 PRXs in Triticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…However, the number of TaSPLs is higher than that of the above species; in particular, there are threefold as many TaSPLs than TuSPLs and AetSPLs. This relationship of TaSPL with TuSPL and AetSPL is consistent with previous studies on the Prx and PK gene family in wheat, T.urartu, and A. tauschii [30]. It is that wheat is allohexaploid, whose origin involved two polyploidization events, and it appears that many gene duplication events occurred in the wheat genome, allowing the number of TaSPLs to increase compared to other species.…”
Section: Characteristics Of Spl Family Genes In Wheatsupporting
confidence: 90%
“…However, the number of TaSPLs is higher than that of the above species; in particular, there are threefold as many TaSPLs than TuSPLs and AetSPLs. This relationship of TaSPL with TuSPL and AetSPL is consistent with previous studies on the Prx and PK gene family in wheat, T.urartu, and A. tauschii [30]. It is that wheat is allohexaploid, whose origin involved two polyploidization events, and it appears that many gene duplication events occurred in the wheat genome, allowing the number of TaSPLs to increase compared to other species.…”
Section: Characteristics Of Spl Family Genes In Wheatsupporting
confidence: 90%
“…Interestingly, we found that TaPRX-2A was localized in the nucleus with NLSs. Some reports have shown that PRX genes such as TaPRXs, AtGPX8, and GPX in mammals and LjGpx1 were located in the cell nuclei [52][53][54][55][56]. It was reported that a barely PRX possess a putative nuclear localization signal, which is located in the nucleus [57].…”
Section: Evolution Of Taprx-2a In T Aestivummentioning
confidence: 99%
“…CIII Prxs are heme-binding proteins that are ubiquitously expressed in all plants and comprise large multigene families [18][19][20][21] . For example, a total of 73 CIII Prxs are present in Arabidopsis thaliana 22,23 , and 138, 374, 93, 94 and 72 have been found in Oryza sativa 24 , Triticum aestivum 25 , Populus trichocarpa 26 , Pyrus bretschneideri 27 and Citrus sinensis 28 , respectively. CIII Prxs regulate the loosening of cell walls, lignification and suberization [29][30][31][32] and participate in ROS and RNS metabolism during abiotic and biotic stress responses [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%